Paternalistic leadership and counterproductive work behavior: mediating role of leader identification and moderating effect of traditionality in Chinese generation Z employees - Ke, Yangjie; Liu, Li; Gu, Manli (Frontiers in Psychology, 2025)
IntroductionThis study investigates how paternalistic leadership (authoritarian, benevolent, and moral) affects counterproductive work behavior among Chinese Generation Z employees. By integrating culturally specific leadership styles with generational traits, this research offers insights into the mechanisms driving counterproductive work behavior in the Chinese workplace. Drawing upon social identity theory and the cultural context of traditional China, we propose a moderated mediation model where leader identification acts as a mediator and the employee’s traditionality serves as a moderator.MethodsWe collected data through a multi-wave survey of 324 Gen Z employees in China. The collected data were analyzed in Stata 17.0 using multiple regression analysis, examining the relationship between paternalistic leadership and counterproductive work behavior.ResultsResults reveal that benevolent and moral leadership reduce counterproductive work behavior, while authoritarian leadership increases it. Leader identification fully mediates the effects of benevolent and moral leadership, and partially mediates the effect of authoritarian leadership. Traditionality negatively moderates the relationship between paternalistic leadership and leader identification, with lower traditionality strengthening this connection.DiscussionThese results highlight the complex dynamics between leadership styles and employee behavior, providing insights for creating productive and harmonious workplaces for Gen Z employees in China. The findings also emphasize leader identification as a key mechanism and traditionality as a contextual moderator shaping these effects, underscoring the need for adaptive leadership approaches.